Creation of a rating system for expert organizations operating in the field of industrial safety expertise - Kotelnikov V.V.; Korotkiy A.A.; Egelskaya E.V. (Научно-технический вестник Брянского государственного университета)
Examination of industrial safety is a tool for industrial safety management of enterprises, which requires high quality of execution of expert works and compliance of expert organizations with the current requirements. The article analyzes the unfavorable factors and trends in the market of expert services and proposes ways to improve their quality by creating a rating system of expert organizations, which allows in the form of information to characterize the expert organization by the main criteria. The proposed system will structure them according to the degree of professionalism and integrity, as well as serve to create a «healthy» competition and information openness for customers, which as a result will affect the reduction of accident rates and accidents during the operation of hazardous production facilities.